Determinants of Sexual and Non-Sexual Risktaking Behaviors of Digital Natives - A. Mata, Kathlyn (International Journal of Psychosocial Rehabilitation, 2020)
This study examines the determinants of sexual and non-sexual risk-taking behaviors of digital natives of a university in Northern Philippines utilizing the descriptive-correlational method of research with a validated structured survey questionnaire as a data-gathering instrument. Findings revealed that the majority of the digital natives were exposed to various means of pornographic materials and had experienced engaging in nonsexual risk-taking behaviors, including drinking alcoholic beverages, cheating in school, and smoking cigarettes. Moreover, most of the independent variables are highly associated with premarital sex (PMS) behavior. Respondents’ age, sex, course, year level, religion, academic performance, and living away from home significantly interrelate to premarital sex behavior. Further, select sex-related circumstances and non-sexual risk-taking behaviors of the digital natives were significantly correlated with PMS. On the select peer-related sexual risk-taking behaviors, only reading pornographic materials was found to be not correlated. Furthermore, the peer-related nonsexual risk-taking behaviors were found to be significantly related to PMS. Hence, with PMS as a critical societal issue, it is but relevant to intensify programs and growth sessions invoking collaborative efforts among the stakeholders in higher education institutions.